Extraction and characterization of coal derived humic acids as soil conditioner - Muhammad Faizal, Md Nor. (Universiti Malaysia Sarawak (UNIMAS), 2005)
Humic acids (HA) were extracted from young Mukah coal using alkaline extraction (NaOH and KOH solution). The humic acids precipitates were separated by centrifugation from its acidified solution. Samples were characterized by the yield, moisture content, ash content, total acidity, -COOH group, -OH group, nitrogen content and E./E6 ratio. The functional groups were identified by FTIR spectroscopy. The properties of the coal-derived humic acids were compared with the properties of humic acids extracted from the nitrated sample which produce through regenerated process.